2015
DOI: 10.1016/j.rser.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A model to evaluate the success of Solar Home Systems

Abstract: Around twenty per cent of the world's population currently do not have access to electricity while the importance of electricity services for society continues to increase. Solar Home and their characteristic of still being an innovation, were also determined. The proposed model of success can be applied to pre-evaluate SHS programmes, to evaluate existing SHS projects, and to observe and evaluate the development of SHS implementation over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…It offers a framework to explore how an innovation is perceived to be consistent with socio-cultural values and helps provide clarity on the innovation decision process experienced by the potential adopter. A number of recent studies have demonstrated the benefits of applying the diffusion of innovations theory as a framework to explore the challenges with scaling renewable energy provision in developing countries (Holtorf, et al, 2015;Urmee 2016;Velayudhan 2003;Zanello, et al, 2016;Mceachern & Hanson 2008), however, none has applied it to analyse the diffusion of PAYG SHS. The aim of this paper is to explore the challenges related to achieving widespread diffusion of PAYG SHS and identify the potential role of policy in overcoming such challenges.…”
Section: Diffusion Of Innovations Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It offers a framework to explore how an innovation is perceived to be consistent with socio-cultural values and helps provide clarity on the innovation decision process experienced by the potential adopter. A number of recent studies have demonstrated the benefits of applying the diffusion of innovations theory as a framework to explore the challenges with scaling renewable energy provision in developing countries (Holtorf, et al, 2015;Urmee 2016;Velayudhan 2003;Zanello, et al, 2016;Mceachern & Hanson 2008), however, none has applied it to analyse the diffusion of PAYG SHS. The aim of this paper is to explore the challenges related to achieving widespread diffusion of PAYG SHS and identify the potential role of policy in overcoming such challenges.…”
Section: Diffusion Of Innovations Theorymentioning
confidence: 99%
“…Even though the household electricity market is predicted to grow rapidly, penetration of SHS remains low and may be considered a niche innovation (Lighting Africa, 2012). A number of SHS programmes have been undertaken in developing countries, yet Holtorf et al,. (2015) highlight that only a few appear to be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Table I summarises the diffusion of innovation framework (Rogers, 2003), which consists of four elements. It has been used in a number of RET diffusion studies (Barrie and Cruickshank, 2017; Holtorf et al , 2015; McEachern and Hanson, 2008; Velayudhan, 2003). It is comprehensive, covering all aspects of the diffusion process from the adopter perspective, but also allows detailed analysis of sub-elements (Helitzer et al , 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is comprehensive, covering all aspects of the diffusion process from the adopter perspective, but also allows detailed analysis of sub-elements (Helitzer et al , 2003). It is flexible and has been used in combination, partially (Barrie and Cruickshank, 2017) or wholly, with other frameworks (Holtorf et al , 2015; McEachern and Hanson, 2008). One of its key strengths is that it allows assessments to be tied back to a body of remedy literature (Helitzer et al , 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another important problem is estimated at around 1.2 billion people worldwide do not have access to electricity from the existing grid [4]. Because most of them live in isolated places, to where extending the grid is uneconomical [5]. And, the use of alternative energy sources like renewable energy (solar, wind) to satisfy the increasing global load.…”
Section: Introductionmentioning
confidence: 99%